A Brand Equity Management in Enhancing School Competitiveness at MIM Unggulan Kota Gorontalo - Irma, Irma Lisdiana; Roskina, Sitti Roskina Mas; Arifin, Arifin (Sustainable Human Capital Development Journal, 2025)
<span id="docs-internal-guid-ab8151bc-7fff-2324-cb71-d4f0cbd50070" style="font-size: 12pt; font-family: Arial, sans-serif; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;">This study aimed to describe: (1) The selling value of MIM Unggulan Kota Gorontalo; (2) The implementation of selling value consistency at MIM Unggulan Kota Gorontalo; and (3) The effectiveness and impact of brand equity management at MIM Unggulan Kota Gorontalo. This research employed a qualitative approach. Data were collected through interviews, observation, and documentation. The data analysis model employed was the interactive analysis model, which involved data condensation, data display, and drawing conclusions. Data validity was tested using source triangulation. The results of this study show that: (1) The central selling values of MIM Unggulan Kota Gorontalo, which build and strengthen the brand equity of “Unggulan,” include: an A accreditation, an innovative curriculum, professional human resources, modern facilities and infrastructure, outstanding extracurricular programs, and various innovative initiatives; (2) The implementation of consistent selling values at MIM Unggulan Kota Gorontalo is carried out through creative and consistent promotional strategies on Facebook, Instagram, TikTok, and YouTube; and (3) The effectiveness of brand equity management at MIM Unggulan Kota Gorontalo has proven to strengthen the brand awareness, brand association, perceived quality, and brand loyalty. This substantial brand equity has become the main competitive advantage of MIM Unggulan Kota Gorontalo.